Exotic looped trajectories of photons in three-slit interference - Omar S Magaña-Loaiza (Nature Portfolio, 2016)
Looped trajectories of photons in a three-slit interference experiment could modify the resulting intensity pattern, but they are experimentally hard to observe. Here the authors exploit surface plasmon excitations to increase their probability, measuring their contribution and confirming Born’s rule.